ANDROID-BASED CLOTH MANAGEMENT APPLICATION - Lai, Chin Chong (Universiti Malaysia Sarawak (UNIMAS), 2015)
The difficulty in managing a large collection of clothes is a common problem faced by many people, especially when there is little time to be spared on it. Complication in handling this tash will lead to other problems such as unmanageable appearance and may affects the daily life of an individual. The conventional way of closet management proves to be time consuming and requires a lot of efforts. Thus, the proposed application is developed in order to solve the problems that arise. Three objectives are specified for the proposed application. This inclu.des the building of a fully fu.netional Android-based cloth management application and the accessibility which is through offline. The scopes ;,ncludes the form for user input, fnnction to trace the use of cloth in term of date of u,se, cloth placement, and recommendation for maintenance with the addition of search utility throu.gh keywords or from the inventory. Apart from that, the implementation phase of this application will adopt the Software Development Life Cycle (SDLC) In this approach, the implementatian will be divided into seven phases, which are planning, analysis, design, pratotyping, develap ment, testing, and evaluation. The flow of this methadology is in linear form where one stage should be completed before moving to. the next stage.